Outbreaks in hematopoietic stem cell transplant units: a systematic review - Kakoullis, Loukas; Chedid, Georges; Walker, Bradley; Xirou, Vasiliki; Hafez, Sufian Abdel; Zisis, Sokratis N.; Arora, Shreya; Christophi, Costas A.; Panos, George; Harris, Courtney E.; Colgrove, Robert (My University, 2025)
Objective: To identify and present the pathogens and sources of contamination linked to outbreaks within hematopoietic stem cell transplant (HSCT) units. Design: Systematic review. Setting: Inpatient HSCT units. Methods: The PubMed/Medline databases were systematically searched as per the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines, employing the search terms “stem cell”, “bone marrow”, “transplant”, “transplantation”, “outbreak” and “pseudo-outbreak” from inception until July 31, 2024. Data on the type of event, pathogen involved, and source of contamination were extracted from eligible publications. Results: In total, 39 studies including 387 patients were included in this review. The overall mortality rate was 23%. Pathogens identified included adenovirus, RSV, Pseudomonas aeruginosa, Aspergillus spp., and non-tuberculous mycobacteria (NTM). P. aeruginosa outbreaks were associated with contaminated sanitary fixtures (P = .007) and water (P = .039), outbreaks caused by NTM were associated with water (P = .009), while Aspergillus spp. outbreaks were associated with construction (P < .001). An index case was identified in 36.8% of viral outbreaks (P = .016). Other sources included inadequate disinfection and transmission from visitors. Conclusions: Our study highlights several associations between pathogens involved in HSCT unit outbreaks and their respective sources. Establishing standardized guidelines for unit construction – particularly for ventilation and water safety – could further reduce the risk of pathogen transmission and enhance infection prevention in these high-risk settings.
Keywords: Adenoviridae; adenovirus infection; adult; antibiotic prophylaxis